Effectiveness of a teaching methodology based on the theory of historical thinking through active methods and digital resources in Spanish adolescents - López-García, Alejandro (Frontiers in Education, 2023)
Twenty-first century education is firmly committed to training young people in new competencies that are transferable to a variety of life situations. Historical thinking as a methodological theory is emerging in a large number of countries. In thinking historically, the skills of the historians are used, so that the sources of the past can be interpreted and the generation of effective historical narratives can be enhanced. This study aims to compare the general perception of the teaching of history between two groups of baccalaureate students, with respect to the effectiveness and transferability of learning historical thinking. Specifically, the existing perception of the implementation of historical thinking competencies is collected after the pre- and post-evaluation of a unit plan developed with 93 students. A quantitative method was used, namely a quasi-experimental design with a non-equivalent control group. The results indicate a substantial improvement in the responses observed in the experimental group, compared to those obtained in the control group. This impact is associated with the didactic methodology implemented with both groups, which showed notable changes in the perception of the theory of historical thinking, as well as in the use of other digital resources and active methods. For the future, it is imperative to transfer these first indications to controlled evaluations of academic outcomes to consolidate the academic status of competency-based teaching in secondary education levels.